Industrial statistics with Minitab - Grima Cintas, Pedro; Marco-Almagro, Lluis; Tort-Martorell Llabres, Javier (Chichester, West Sussex, United Kingdom : Wiley, 2012)
"Industrial Statistics with MINITAB demonstrates the use of MINITAB as a tool for performing statistical analysis in an industrial context. This book covers introductory industrial statistics, exploring the most commonly used techniques alongside those that serve to give an overview of more complex issues. A plethora of examples in MINITAB are featured along with case studies for each of the statistical techniques presented."--
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Minitab; Minitab; Minitab; Minitab; Industrial statistics; Industrial management -- Statistical methods -- Computer programs; Statistics -- Computer programs; Industrial statistics; Industrial management -- Statistical methods -- Computer programs; Statistics -- Computer programs; COMPUTERS -- Mathematical & Statistical Software; Industrial management -- Statistical methods -- Computer programs; Industrial statistics; Statistics -- Computer programs; Industrial statistics; Industrial management / Statistical methods / Computer programs; Statistics / Computer programs; Electronic books; Electronic books